Effects of postnatal growth restriction and subsequent catch-up growth on neurodevelopment and glucose homeostasis in rats. Issue 1 (December 2015) - Alexeev, Erica; Lönnerdal, Bo; Griffin, Ian
Abstract Background There is increasing evidence that poor growth of preterm infants is a risk factor for poor long-term development, while the effects of early postnatal growth restriction are not well known. We utilized a rat model to examine the consequences of different patterns of postnatal growth and hypothesized that early growth failure leads to impaired development and insulin resistance. Rat pups were separated at birth into normal (N, n = 10) or restricted intake (R, n = 16) litters. At d11, R pups were re-randomized into litters of 6 (R-6), 10 (R-10) or 16 (R-16) pups/dam. N pups remained in litters of 10 pups/dam (N-10). Memory and learning were examined through T-maze test. Insulin sensitivity was measured by i.p. insulin tolerance test and glucose tolerance test. Results By d10, N pups weighed 20 % more than R pups (p  < 0.001). By d15, the R-6 group caught up to the N-10 group in weight, the R-10 group showed partial catch-up growth and the R-16 group showed no catch-up growth. All R groups showed poorer scores in developmental testing when compared with the N-10 group during T-Maze test (p  < 0.05). Although R-16 were more insulin sensitive than R-6 and R-10, all R groups were more glucose tolerant than N-10. Conclusion In rats, differences in postnatal growth restriction leads to changes in development and in insulin sensitivity. These results may contribute to better elucidating the causes of poor developmental outcomes in human preterm infants.